2009
DOI: 10.1590/s0103-90162009000400002
|View full text |Cite
|
Sign up to set email alerts
|

Water relations of field-grown grapevines in the São Francisco Valley, Brazil, under different rootstocks and irrigation strategies

Abstract: There is an increased demand for high quality winegrapes in the São Francisco Valley, a new wine producing area in Brazil. As the grape quality is closely linked to the soil water status, understanding the effects of rootstock and irrigation management on grapevine water relations is essential to optimize yield and quality. This study was carried out to investigate the effects of irrigation strategies and rootstocks on water relations and scion vigour of field-grown grapevines in Petrolina, Pernambuco state, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…Applying this method for irrigation scheduling requires knowledge about temporal variations of soil water contents (SWCs) at the field scale for crops both under optimal or water-stress conditions in a soil-plant continuum. This is because the plant water status, which is a dominant factor determining the crop yield (Taiz and Zeiger, 2006), is closely related to SWC (Dorji et al, 2005;Simon et al, 2009;Souza et al, 2009;Stoll et al, 2000;Xu, 2009). Thus, in order to achieve the highest irrigation water use efficiency, the reduction of irrigation should be done only to the extent that SWC is kept under optimal conditions to avoid a significant reduction in yield.…”
Section: Introductionmentioning
confidence: 99%
“…Applying this method for irrigation scheduling requires knowledge about temporal variations of soil water contents (SWCs) at the field scale for crops both under optimal or water-stress conditions in a soil-plant continuum. This is because the plant water status, which is a dominant factor determining the crop yield (Taiz and Zeiger, 2006), is closely related to SWC (Dorji et al, 2005;Simon et al, 2009;Souza et al, 2009;Stoll et al, 2000;Xu, 2009). Thus, in order to achieve the highest irrigation water use efficiency, the reduction of irrigation should be done only to the extent that SWC is kept under optimal conditions to avoid a significant reduction in yield.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism for grapevine scion vigor controlled by rootstocks is poorly understood, several authors have shown effects on water relations (Souza et al, 2009), gas exchange (Soar et al, 2006), vegetative vigor (Keller et al, 2001), yield and grape quality (Nuzzo and Mathews, 2006). Therefore, the selection of an appropriate rootstock may provide a powerful tool for managing the growth and fruiting of grapevine scions subjected to the double pruning technique.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in plants that are routinely grafted, such as grapevine (Vitis vinifera L.), rootstock effect on scion performance must be considered in the study of adaptability to stress conditions. Rootstocks provide tolerance to exogenous limiting factors, biotic (e.g., soilborne pests) and abiotic (e.g., salinity, water or oxygen deficit), while influencing the ecophysiological behaviour of the scion and its berry quality (Bavaresco and Lovisolo, 2000;Padgett-Johnson et al, 2000;Soar et al, 2006;Tramontini et al, 2012;de Souza et al, 2009;Ibacache and Sierra, 2009;Rizk-Alla et al, 2011;Marguerit et al, 2012). Stomata are considered direct responsible of optimizing the balance between carbon gain and water loss of the plant (Rogiers et al, 2012), and the patterns of their response, in terms of timing and intensity, are genetically determined (Chaves et al, 2010).…”
Section: Introductionmentioning
confidence: 99%